Data Mining Prediksi Minat Calon Mahasiswa Memilih Perguruan Tinggi Menggunakan Algoritma C4.5 - Chairun Nas (Jurnal Manajemen Informatika (JAMIKA), 2021)
The city of Cirebon has many diverse private universities and offers a variety of majors. Due to a large number of existing private universities, the competition between universities to attract prospective new students is very tight. So to be able to compete with these universities, the campus needs to predict the interest of prospective new students by knowing what factors are driving prospective new students to choose colleges. The purpose of this study was to predict the interest of prospective students in choosing a college. In this study, the data processed are the results of a survey conducted on prospective new students in the D3-Informatics Management Study Program. There are 25 sample data as training datasets with 5 assessment data. The data will be processed using the Data Mining process with the Classification Method. Furthermore, with the C4.5 algorithm in the Classification method, iterations are obtained up to node 4 with 3 assessment data which are factors in determining the interest of prospective students in the study program. Furthermore, the results of data processing using the classification method with the C4.5 algorithm were tested using Rapid Miner Software, which obtained a 100% accuracy rate with 120 testing datasets. The final result of using Data Mining with the C4.5 algorithm has been able to predict the interest of prospective new students based on assessment factors in choosing universities.